A generalized, non-pruritic variant of lichen amyloidosis: A case report and a brief review - Rajat Kandhari; V Ramesh; Avninder Singh (Wolters Kluwer Medknow Publications, 2013)
Lichen amyloidosis (LA) has been considered a highly pruritic dermatosis, and the deposition of fibrillar material has generally been considered to be secondary to the scratching. Focal epidermal damage and chronic scratching have been implicated as the pathogenetic factors in the occurrence of LA, although they may not be able to explain the occurrence of a widespread variant of this dermatosis. There are few case reports describing the occurrence of a non-pruritic variant of LA. We hereby report a case of non-pruritic, generalized variant of lichen amyloidosis.